2007
DOI: 10.1175/2007jas2317.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Occurrence of Hollow Bullet Rosette– and Column-Shaped Ice Crystals in Midlatitude Cirrus

Abstract: Cirrus clouds in mid-and high latitudes are frequently composed of bullet rosette-and column-shaped ice crystals, which can have hollow ends. Bullet rosette-shaped ice crystals are composed of a number of bullets radiating from a central point. Research has shown that the light-scattering properties of ice particles with hollow ends are different from the scattering properties of solid ice particles. Knowledge of the frequency of occurrence of hollow particles is important to more accurately calculate the radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
3
23
0
Order By: Relevance
“…Compact aggregates and spatial bullet rosettes are also seen and tend to be more common in the midlatitudes (Um and McFarquhar, 2007). Some of the particles observed by the CPI probe appear to have hollow structures, a feature noted by Magono and Lee (1966), Schmitt and Heymsfield (2007), Baran (2012), and Yang et al (2008c, specifically, the photograph by Steven Warren shown in Fig. 1 of this reference).…”
Section: Introductionmentioning
confidence: 73%
“…Compact aggregates and spatial bullet rosettes are also seen and tend to be more common in the midlatitudes (Um and McFarquhar, 2007). Some of the particles observed by the CPI probe appear to have hollow structures, a feature noted by Magono and Lee (1966), Schmitt and Heymsfield (2007), Baran (2012), and Yang et al (2008c, specifically, the photograph by Steven Warren shown in Fig. 1 of this reference).…”
Section: Introductionmentioning
confidence: 73%
“…The featureless phase functions are known to be related to crystals with mesoscopic surface roughness, aggregates and particles with inclusions. Consequently, surface roughness and internal structure have gained recognition as important factors in the scattering properties of ice crystals [42][43][44][45][46][47]. These small scale features cannot be accurately determined from cloud probe images and consequently may be overlooked in particle models.…”
Section: Introductionmentioning
confidence: 99%
“…Recent laboratory data reveal that most ice particles at low temperatures (2408 to 2708C) have columnar shapes (with variable aspect ratio length/diameter) and that the very small crystals growing at low ice supersaturation are compact faceted polycrystals (Bailey and Hallett 2009). Often ice particles are hollow (Weickmann 1945;Schmitt and Heymsfield 2007). Ice particles may result from homogeneous freezing of initially liquid (water or solution) droplets, which then grow by deposition of water vapor.…”
Section: Introductionmentioning
confidence: 99%